Impact of membrane protein-lipid interactions on formation of bilayer lipid membranes on SAM-modified gold electrode. (20th March 2021) - Kato, Masaru; Masuda, Yuya; Yoshida, Narumi; Tosha, Takehiko; Shiro, Yoshitsugu; Yagi, Ichizo
Highlights: A protein-tethered bilayer lipid membrane (ptBLM) was assembled on SAM/Au. The ptBLM assembly was monitored by time-resolved SEIRA spectroscopy. The lipid bilayer formation kinetics was influenced by protein–lipid interactions. Protein–lipid interactions improved the electrocatalytic stability of the cNOR. Abstract: In protein film electrochemistry for redox-active membrane proteins, the reconstitution of protein-tethered bilayer lipid membranes (ptBLMs) can maximize their functionality and stability at electrolyte/electrode interfaces. To understand the impact of protein–lipid interactions on the ptBLM formation, we tracked the reconstitution process of a lipid bilayer in the presence or the absence of a transmembrane enzyme of cytochrome c -dependent nitric oxide reductase (cNOR) on a mixed self-assembled monolayer (SAM)/Au electrode. Time-resolved surface-enhanced infrared absorption (SEIRA) spectroscopy and electrochemical measurements revealed that the protein–lipid interaction affected the formation kinetics for the phospholipid bilayer and the electrocatalytic stability of the cNOR-modified electrode but not the fluidity of the phospholipid bilayer. Graphical abstract: Image, graphical abstract